Sistem Absensi Mapel Lintas Minat SMAN 1 Cigombong Menggunakan Face Recognition Berbasis Web - Lucia Kharisma, Ivana; Sahira, Sarah; Nurcahya Sumirat, Hana; Fergina, Anggun; Kamdan, Kamdan (Computer Science and Information Technology, 2024)
SMAN 1 Cigombong is a high school located on Watesjaya Street, Cigombong District, Bogor Regency, West Java, which currently still follows the KURTILAS curriculum. The student attendance system in SMAN 1 Cigombong for the English and German Language Minors is still using a manual attendance book where students sign the attendance form. This method has weaknesses such as the ease of losing or damaging the attendance book, as well as the potential for students to manipulate the attendance records. Therefore, the author proposes the implementation of a face recognition attendance system to assist in the attendance data recording process, simplify attendance tracking for teachers, and facilitate the school's management information system. The development method used for the attendance system is the waterfall method, which involves analysis, design, coding, testing, and support stages. In face recognition, the author utilizes face landmarks to store students' facial data in a database. Meanwhile, in the data collection process, several methods are used, including interviews, observations, and literature reviews.